2012
DOI: 10.3126/kumj.v10i1.6905
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Rapid Test for Diagnosis of Dengue in Nepalese Patients during 2010 Epidemic

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This was a systematic review addressing the dengue virus detection methods in commercially available ICTs, obtained through a search of nine large databases, with 57 studies included. One strategy used to increase the tests' performance was the simultaneous test of the three analytes NS1, IgM, and IgG 40,46,56,58,67,71 . In our review, these ICTs showed high pooled estimates, better than those of IgA ICTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a systematic review addressing the dengue virus detection methods in commercially available ICTs, obtained through a search of nine large databases, with 57 studies included. One strategy used to increase the tests' performance was the simultaneous test of the three analytes NS1, IgM, and IgG 40,46,56,58,67,71 . In our review, these ICTs showed high pooled estimates, better than those of IgA ICTs.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, we reviewed 3,783 abstracts, and selected 108 articles for reading the full-texts, of which 57 were selected for this review (Figure 1). The studies assessed multiple ICT brand tests with different analytes: five assessed IgA 24,25,26,27,28 , 21 NS1 10,27,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 , 12 IgM/IgG 27,34,48,49,50,51,52,53,54,55,56,57 , and 25 NS1/IgM/IgG 29,36,37,40,46,58,59,60,61,62,63,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…from Nepal evaluated Bioline Dengue Duo and reported a sensitivity and specificity of 70% and 76%, respectively; they further concluded that overall performance of the rapid test is poor and other options should be explored for early diagnosis of dengue virus infection. [20] Bioline Dengue Duo kit for antidengue IgM antibody has been evaluated extensively by many workers with conflicting results. Mai et al .…”
Section: Discussionmentioning
confidence: 99%
“…The failure to detect dengue cases with potential signs of deterioration (warning signs) may lead to the increased risk of dengue mortality. Several studies have showed that early detection of warning signs and appropriate fluid management contributes to good patient outcomes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%